2008
DOI: 10.1055/s-2008-1067537
|View full text |Cite
|
Sign up to set email alerts
|

Psychische Folgen eines Früh- und Spätabortes in der Folgeschwangerschaft – eine Pilotuntersuchung

Abstract: Women who have suffered from perinatal loss do not score higher on depression, anxiety or general psychopathology during subsequent pregnancies than women without loss experience. Only a minority of women, who have suffered from loss show ongoing signs of unresolved mourning. However, in order to detect criteria for the identification of those who might be at risk during subsequent pregnancies studies with larger samples size are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…For sociodemographic factors such as age, for example, a study on depression symptoms among pregnant women in the middle and third trimesters showed that the younger they are, the higher the positive rate of depression symptoms they have. 7 Pregnancy characteristics such as planned pregnancy, 8 history of abortion 9 and personality traits such as low self-efficacy were related to prenatal depression. 10 Psychosocial factors such as socioeconomic status, social support and life events were associated with mental health during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…For sociodemographic factors such as age, for example, a study on depression symptoms among pregnant women in the middle and third trimesters showed that the younger they are, the higher the positive rate of depression symptoms they have. 7 Pregnancy characteristics such as planned pregnancy, 8 history of abortion 9 and personality traits such as low self-efficacy were related to prenatal depression. 10 Psychosocial factors such as socioeconomic status, social support and life events were associated with mental health during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Hier wurden unter anderem die folgenden Risikofaktoren untersucht: Vaterlosigkeit [46], inkonsistentes Erziehungsverhalten [15], geringes elterliches Engagement [15], geringes Monitoring der Eltern [24], Substanzgebrauch der Eltern [24], sozial auffällige Freunde [24], Ethnizität [17] sowie kritische bzw. traumatische Lebensereignisse wie Früh− und Spätaborte, Ausbombung und Flucht / Vertreibung im Krieg [31,38,39,47,49]. Bei der Einschätzung von Entwicklungsrisiken ist es wichtig, zu− sätzlich zu den Risikofaktoren sogenannte Schutzfaktoren sowie das Zusammenwirken beider zu berücksichtigen [52].…”
Section: Risiko− Und Schutzfaktorenunclassified
“…There are several studies about the influencing factors for depressive symptoms in western countries [7][8][9][10][11]. It is reported that factors related to depressive symptoms in pregnant women included history of depression, negative obstetric experiences, lack of social support, low education, and alcohol consumption and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Another studie [21] showed that the longer the number of years of schooling, the higher the risk of depression, while some studies reported no associations between years of schooling and depression [16,22,23]. Pregnancy characteristics such as planned pregnancy [7], history of abortion [8] and Psychosocial factors such as socioeconomic status, studies have found that socioeconomic factors are closely associated with the risk of depressive symptoms in pregnant women [24,25]. However, some previous studies did not observe this association [26,27].…”
Section: Introductionmentioning
confidence: 99%